Organic contaminants in marine environment - Let us not forget the shallow areas - Hardoim, Cristiane Cassiolato Pires [UNESP]; Ramaglia, Andressa Cristina [UNESP]; da Silva, Josilene; Taniguchi, Satie; Lourenço, Rafael André (Elsevier, 2021)
The evaluation of anthropogenic pressures in marine environments commonly involves sediments, water and marine biota. However, the evaluation of the quality of the beach sediment and sediments from shallow areas are scarce compared to sediments from deeper areas in environmental assessment studies. In this study polycyclic aromatic hydrocarbons and linear alkylbenzenes were assessed in sediments from shallow areas of the São Sebastião channel, southeastern Brazil. The channel is part of the Marine Protected Area of the Northern Coast of São Paulo State besides holds the largest petroleum terminal in South America further than three sewage outfalls. Despite the concentrations of these contaminants in the sediments were relatively low compared to those found in the sediments from deeper areas of the channel, suggesting low toxicity of the beach sediments, the contamination reflected the pattern of the sediments of the São Sebastião channel.
Keywords: Linear alkylbenzenes; Polycyclic aromatic hydrocarbons; Sediments; Shallow areas; São Sebastião